Functional roles of microbial symbionts in plant cold tolerance - Acuña Rodríguez, Ian S.; Newsham, Kevin K.; Gundel, Pedro Emilio; Torres Díaz, Cristian; Molina Montenegro, Marco A. (Ecology Letters)
In this review, we examine the functional roles of microbial symbionts in plant tolerance to cold and freezing stresses. The impacts of symbionts on antioxidant activity, hormonal signaling and host osmotic balance are described, including the effects of the bacterial endosymbionts Burkholderia, Pseudomonas and Azospirillum on photosynthesis and the accumulation of carbohydrates such as trehalose and raffinose that improve cell osmotic regulation and plasma membrane integrity. The influence of root fungal endophytes and arbuscular mycorrhizal fungi on plant physiology at low temperatures, for example their effects on nutrient acquisition and the accumulation of indole-3-acetic acid and antioxidants in tissues, are also reviewed. Meta-analyses are presented showing that aspects of plant performance (shoot biomass, relative water content, sugar and proline concentrations and Fv/Fm) are enhanced in symbiotic plants at low (−1 to 15 °C), but not at high (20–26 °C), temperatures. We discuss the implications of microbial symbionts for plant performance at low and sub-zero temperatures in the natural environment and propose future directions for research into the effects of symbionts on the cold and freezing tolerances of plants, concluding that further studies should routinely incorporate symbiotic microbes in their experimental designs. Fil: Acuña Rodríguez, Ian S. Universidad de Talca; Chile Fil: Newsham, Kevin K. British Antarctic Survey; Reino Unido Fil: Gundel, Pedro Emilio. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Instituto de Investigaciones Fisiológicas y Ecológicas Vinculadas a la Agricultura. Universidad de Buenos Aires. Facultad de Agronomía. Instituto de Investigaciones Fisiológicas y Ecológicas Vinculadas a la Agricultura; Argentina Fil: Torres Díaz, Cristian. Universidad del Bio Bio; Chile Fil: Molina Montenegro, Marco A. Universidad de Talca; Chile